2009
DOI: 10.1016/j.ijgo.2009.03.008
|View full text |Cite|
|
Sign up to set email alerts
|

Low‐dose propofol to prevent nausea and vomiting after laparoscopic surgery

Abstract: Prophylactic therapy with 0.5 mg/kg of propofol was found to be effective in preventing nausea/vomiting in patients undergoing gynecologic laparoscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Small dose (0.5 mg kg -1 ) of propofol administered i.v. at the end of surgery was effective for preventing PONV in women undergoing gynecologic laparoscopic surgery [84]. By contrast, Montgomery et al found no effect of subhypnotic dose (0.1 mg kg -1 h -1 ) of propofol infusion for 24 h postoperatively in women undergoing major gynecological surgery [17].…”
Section: Propofol Dexamethasone and Ephedrinementioning
confidence: 97%
“…Small dose (0.5 mg kg -1 ) of propofol administered i.v. at the end of surgery was effective for preventing PONV in women undergoing gynecologic laparoscopic surgery [84]. By contrast, Montgomery et al found no effect of subhypnotic dose (0.1 mg kg -1 h -1 ) of propofol infusion for 24 h postoperatively in women undergoing major gynecological surgery [17].…”
Section: Propofol Dexamethasone and Ephedrinementioning
confidence: 97%
“…However, a recent study in patients undergoing gynecological laparoscopy found that bolus doses of propofol 0.5 mg/kg administered at the end of surgery were effective in reducing PONV, when compared to placebo. [ 39 ] Lower doses than this were not effective.…”
Section: Antiemeticsmentioning
confidence: 99%
“…Propofol은 5-HT3 수용체 차단제의 역할 [13] 또는 중추신 경계의 화학수용체 방아쇠 영역과 오심 및 구토와 관련된 미주신경 등의 직접적인 억제 작용을 통해 [14] PONV 예방 및 치료에 효과가 있다고 하나, 마취 유도제로 쓰였을 경우의 PONV 예방 효과에 대해서는 여러 가지 이견이 있다 [5,[15][16][17][18][19][20][21]. Values are number of patients.…”
unclassified